Concepções historiográficas e ensino de História: representações das práticas docentes (Caxias do Sul/RS: 1997-2019) - Freitas, Aline Marques de (My University, 2020)
This research was executed within the Postgraduate Program in Education at the University of Caxias do Sul, part of the History and Philosophy of Education field. This study aims to investigate the representations that teachers build about their History teaching-learning practices, correlating with historiographic conceptions, in the context of the municipal education network in Caxias do Sul (RS-BR), between 1997 and 2019. The temporal cut is justified by the validity of the Brazilian Educational Standards (Parâmetros Curriculares Nacionais), fixed in 1997, until the establishment of the National Educational Standards Base (BNCC ? Base Nacional Comum Curricular) in the municipal education network of Caxias do Sul. The research, which anchors in the History of Education field, aimed to describe and analyze the representations of teachers about their practices, especially with regard to the historiographic conceptions that emerge from these representations (CHARTIER, 1988, 2011). The analysis of practices as a creation of the teacher between his knowledge (TARDIF, 2007) and his strategies and tactics (CERTEAU, 1994) was understood as the work of an intellectual mediator (GOMES; HANSEN, 2016). The empiricism was built based on two procedures: online questionnaire and survey as well as in-depth interviews. Twenty-three teachers answered the questionnaire. In-depth interviews were conducted with five teachers, following the method of Oral History (ALBERTI, 2004; ERRANTE, 2000). The empiric corpus was analyzed (MORAES and GALIAZZI, 2013; MORAES, 2003) in relation to historiographic conceptions, due to their semantic approaches, considering that the teacher has an argumentative knowledge (TARDIF, 2007) that is developed in the discursive activity, validated by linguistic operations, which implies another individual and goes through communicational agreements within the discussion community. Therefore, for the analysis, it was necessary to describe how historiographic conceptions were understood by teachers, along with which relationships they have with the multiple objects of work of the teacher. History teachers represent themselves as materialists, even if they agree with the conceptions of New History, maintaining a relationship of otherness with the positivist conceptions. In general, their educational background, represented as aligned with positivist conceptions, form the set of knowledge of what they do not want to reproduce. Their professional training is represented as linked to materialist conceptions and this was expressed in their conceptual argument. They work with prescriptive documents that are more connected with historiographic renewal and this is manifested in their practices, understood as playful, and not in their knowledge-building power. These historiographical conceptions are not understood in their theoretical "boxes", and, even though, they support their choices, as they can be adapted to the intended purposes. Teachers mediate their knowledge in their practices, of which historiographic conceptions are part, not understood in their theoretical "boxes" but supporting their choices as they may be appropriate to the intended educational purposes [resumo fornecido pelo autor].
Essa pesquisa se desenvolveu junto ao Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul, vinculada a Linha História e Filosofia da Educação. O estudo investiga representações que os professores constroem sobre suas práticas de ensino-aprendizagem de História, correlacionando com as concepções historiográficas, no contexto da rede municipal de educação de Caxias do Sul (RS), entre os anos de 1997 e 2019. O recorte temporal é justificado pela vigência dos Parâmetros Curriculares Nacionais, instituídos em 1997, até estabelecimento da Base Nacional Curricular Comum (BNCC) na rede municipal de educação em Caxias do Sul. A pesquisa, no campo da História da Educação, apoiada no referencial teórico da História Cultural, teve como objetivo descrever e analisar as representações dos professores sobre suas práticas, principalmente no que se refere às concepções historiográficas que emergem a partir dessas representações (CHARTIER, 1988, 2011). A análise das práticas como uma criação do professor entre seus saberes (TARDIF, 2007) e suas estratégias e táticas (CERTEAU, 1994) foi entendida como um trabalho de um intelectual mediador (GOMES; HANSEN, 2016). A empiria foi construída a partir de dois procedimentos: questionário on-line e entrevistas em profundidade. O questionário foi respondido por vinte e três professores. As entrevistas em profundidade foram realizadas com cinco professores, seguindo a metodologia da História Oral (ALBERTI, 2004; ERRANTE, 2000). A empiria foi analisada (MORAES e GALIAZZI, 2013; MORAES, 2003) na relação com as concepções historiográficas, por suas aproximações semânticas, considerando que o professor possui um saber argumentativo (TARDIF, 2007) que se desenvolve na atividade discursiva, validado por operações linguísticas, que implica um outro e passa por acordos comunicacionais dentro da comunidade de discussão. Por isso, para essa análise foi preciso descrever como as concepções historiográficas são entendidas pelos professores, bem como quais as relações que elas possuem com os múltiplos objetos de trabalho do professor. Os professores de História se representam como materialistas, mesmo que concordem com as concepções da Nova História, mantendo uma relação de alteridade com as concepções positivistas. No geral, sua formação escolar, representada como alinhada às concepções positivistas, forma o conjunto de saberes do que não querem reproduzir. A sua formação profissional é representada como ligada às concepções materialistas e isso se expressa na sua argumentação conceitual. Trabalham com documentos prescritivos mais alinhados à renovação historiográfica e isso se manifesta nas suas práticas, entendidas como lúdicas, e não na sua potência de construção de conhecimento. Os professores mediam nas suas práticas seus saberes, da qual fazem parte as concepções historiográficas, não entendidas nas suas "caixas" teóricas e sim amparando as suas escolhas conforme podem ser adequadas às finalidades educativas pretendidas [resumo fornecido pelo autor].
Keywords: Educação - História; Historia - Caxias do Sul (RS) - Estudo e ensino; Historiografia; Professores - Formação; Abordagem interdisciplinar do conhecimento na educação; Education - History; History - Caxias do Sul (Brazil) - Study and teaching; Historiography; Teachers, Training of; Interdisciplinary approach to knowledge in education